Thermal, mechanical, morphological and aesthetical properties of rotational molding PE/pine wood sawdust composites - Martins, Carla I. (2022)
This research addresses the importance of pine wood sawdust granulometry on the processing of medium-density polyethylene (MDPE)/wood composites by rotational molding and its effects on the morphological, mechanical and aesthetical properties of parts, aiming to contribute for the development of sustainable wood polymer composites (WPC) for rotational molding applications. Pine wood sawdust was sieved (<150, 150, 300, 500, 710, >1000 µm) and analyzed for its physical, morphological and thermal characteristics. Rotational molded parts were produced with matrix/wood ratios from 90/10 to 70/30 wt% considering different wood granulometries. As a natural material, wood changed its color during processing. Granulometries below 500 µm presented better sintering, homogeneity and less part defects. Furthermore, 300–500 µm favored the impact resistance (1316 N), as irregular brick-shaped wood was able to anchor to PE despite the weak interfacial adhesion observed. The increase of wood content from 10 to 30% reduced the impact properties by 40%, as a result of a highly porous structure formed, revealing sintering difficulties during processing. WPC parts of differentiated aesthetics and functionalities were achieved by rotational molding. A clear relationship between wood granulometry and WPC processing, structure and properties was identified.